DIGITAL PEDAGOGY IN THE 21ST CENTURY: LEVERAGING TECHNOLOGY FOR EFFECTIVE ONLINE TEACHING (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the dynamic landscape of digital pedagogy in the 21st century, focusing on how educators can leverage technology to enhance online teaching effectiveness. The rapid evolution of technology has reshaped educational paradigms, making online learning increasingly prevalent. In this context, the article discusses innovative strategies, tools, and best practices for delivering high-quality education in virtual environments. It highlights the role of digital pedagogy in engaging students, promoting active learning, and addressing the diverse needs of online learners. By examining the intersection of technology and pedagogy, this article provides valuable insights for educators navigating the digital age of education.